Can a Patient use an App at Home to Measure Knee Range of Motion? Utilizing a Mobile App, Curovate, to Improve Access and Adherence to Knee Range of Motion Measurements - Nirtal Shah; Corey Grunberg; Zahra Hussain (North American Sports Medicine Institute, 2022)
# Introduction Knee range of motion is a critical measure of progress after knee injury and knee surgery. However, many patients do not understand the importance of knee range of motion and most do not have a way to self-monitor their knee range of motion at home. The patient being able to measure their own range of motion can provide improved access to this critical health metric, and could improve adherence with their daily knee range of motion exercises. The purpose of this technical report is to determine if a mobile app, Curovate, can provide reliable measures of knee range of motion compared to standard goniometric measurements. # Procedures There were four positions of knee flexion and four positions of knee extension each measured twice with a standard goniometer and four different mobile devices with the app Curovate. The reliability and validity of the Curovate app was tested across mobile devices and operating systems and compare to goniometric knee range of motion measurements. A total of 80 measurements were taken. All testing was completed on a healthy 23-year-old male with no knee pathology. # Results A strong positive correlation, Pearson's r > = 0.9985, for all positions of knee flexion and extension across all four mobile devices as well as each mobile device compared to standard goniometric measurements. # Conclusions This article presents a unique method for patients to measure their knee range of motion using the mobile app Curovate. Overall, the mobile app, Curovate, was found to have a strong positive correlation across four mobile devices with varying operating systems and compared to goniometric measurements. # Level of evidence 4